ANALYSIS OF THE INFLUENCE OF INFLATION RATE, INCOME OF SHARIA PAWNSHOPS, AND GOLD PRICES ON RAHN CREDIT DISTRIBUTION AT PT. PEGADAIAN SYARIAH IN INDONESIA (2019–2023) - Ahmad Dahrul Dalimunthe Nurwani; Nurwani; Yanti Nursantri (I-Economics: A Research Journal on Islamic Economics)
This study aims to analyze whether the inflation rate, company revenue, and gold price have an influence on Rahn lending at PT Pegadaian Syariah Indonesia. This research methodology is quantitative. Financial reports, BPS, and Statistical Reports of Indonesian Specialized Financial Institutions published by the Financial Services Authority (OJK) between 2019 and 2023 are the secondary data sources used in this study. SPSS software was used to process the data for this study. Multiple linear regression analysis, traditional hypothesis testing, and hypothesis testing (statistical test/partial test, f/simultaneous test, and coefficient of determination test) are some of the data analysis methods used in this study. The result of this study are; the distribution of Rahn pawn is negatively affected by the inflation variable, the pawnshop income variable has a good influence on pawnshop distribution, and the gold price volatility variable has a positive effect on the distribution of rahn pawn